Application of geophysical prospecting methods in karst exploration - Wang, Shaobo; Xu, Lei; Li, Peng; Wang, Siyuan; Lu, Lifeng; Li, Zhengliang (Frontiers in Earth Science, 2025)
When conducting engineering construction in karst-developed regions, the presence of concealed underground karst systems can easily induce geological hazards such as ground collapse and foundation settlement, posing serious threats to engineering safety. Therefore, it is imperative to ascertain critical information including the degree of karst development and spatial distribution characteristics within the project area. Geophysical prospecting methods, characterized by high efficiency, cost-effectiveness, and strong detection accuracy, have proven to be an effective technical approach for karst exploration. This paper systematically examines several geophysical methods and their detection effectiveness for cavities with different filling states. The research outcomes can provide valuable references for karst investigation in similar engineering projects.